DIFFERENCES IN TIME OF START REACTION AND ACHIEVED RESULT IN THE SPRINT DISCIPLINES IN THE FINALS OF THE OLYMPIC GAMES IN LONDON AND THE WORLD CHAMPIONSHIP IN MOSCOW - Ratko Pavlović (Sport Scientific And Practical Aspects, 2025)
In the sprint events a very important place take the start and start acceleration which is largely generated by the final score. Depending on the appropriate individual morphological dimension, especially motor and functional abilities of competitors, good possibility to implement these parameters is certain. However, despite the excellent results they achieve, differences in these two parameters are evident, which in terms of the final result has a certain effect. The aim of this study was to determine the differences in the starting reaction time and results in the sprint events of the finalists at the Olympic Games in London in 2012. and World Championship in Moscow 2013. The results from the finalists (48 male) and 48 (female) participants were analysed that participated in the final races in the 100m, 200m and 400m. The evaluation of starting reaction time (ms) and results in a sprint (s) based on the reports that were officially published by the International Association of Athletics Federations (IAAF). Results of the analysis of T-test have shown statistically significant differences between the reaction time female finalists of the Olympic Games and World Championships, in the running events of 100m (t= -3.103; p<0.001) and 400m (t= -4.235; p<0.001), in contrast to of the male finalists are significant differences noted in running 200m (t=2.370; p<0.001) and 400m (t= -4.437; p<0.001). Only in the final 100m (Moscow) and 200m (London) were no statistical differences between athletes. Also in the men's final 100m (London) and 200m (Mocow) and the final 100m (Moscow) and 400m (London) are not achieved statistical differences in the time of start of the reaction. The differences in results are achieved (London-Moscow) are realized only in the final race, the female athletes 200m (t=-2.041; p <0.01), while in male athletes this was not the case.